2019
DOI: 10.1563/aaid-joi-d-17-00258
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Initial Wound Healing and Osteogenesis of Porous Tantalum Trabecular Metal and Titanium Alloy Materials

Abstract: Porous tantalum trabecular metal (PTTM) has long been used in orthopedics to enhance neovascularization, wound healing, and osteogenesis; recently, it has been incorporated into titanium alloy dental implants. However, little is known about the biological responses to PTTM in the human oral cavity. We have hypothesized that, compared with conventional titanium alloy, PTTM has a greater expression of genes specific to neovascularization, wound healing, and osteogenesis during the initial healing period. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In the research work presented here, we confirm the positive impact of tantalum on bone-like matrix formation and mineralization. A recent clinical study demonstrated that porous Ta dental implants induced an upregulation of specific genes implicated in neovascularization and osteogenesis, compared to Ti implants [42]. Our data confirm clinical studies that elucidate advantages of Ta implants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the research work presented here, we confirm the positive impact of tantalum on bone-like matrix formation and mineralization. A recent clinical study demonstrated that porous Ta dental implants induced an upregulation of specific genes implicated in neovascularization and osteogenesis, compared to Ti implants [42]. Our data confirm clinical studies that elucidate advantages of Ta implants.…”
Section: Discussionsupporting
confidence: 85%
“…The rarity of Ta, and subsequent high manufacturing cost, had limited its applications in medical fields. However, porous Ta produced via chemical vapor deposition of commercially pure Ta onto a vitreous carbon is currently available for use in orthopedic applications, and porous tantalum trabecular metal (PTTM) has been used in orthopedic implants for several years [42]. Tantalum has recently been tried for incorporation into Ti or coating onto Ti alloy [38,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hefni et al [ 27 ] implanted PTTM into mandibles of osteopenic patients to assess the osteoinductivity of Ta; up-regulation of BMP4 was observed at 2 weeks after implantation. And Bencharit et al [ 10 ] reported better bone defects repair, as well as higher expressions of BMP 3, 4, 5, 7 in the Ta group than that of the Ti alloy group. Besides pure Ta implants, Ta coating on polyetheretherketone (PEEK) by plasma spray was also reported to enhance osteogenic properties of PEEK implants, with higher expression of BMP2 and Runx2 gene than that of the noncoated PEEK group [ 19 , 26 ].…”
Section: Osteogenesis Signaling Pathways Related To Tamentioning
confidence: 99%
“…Besides the above-mentioned signaling pathways, Ta was reported to promote osteogenic differentiation and osteogenesis via some other mechanisms, such as the MAPK signaling pathway mediated by oxidative stress [ 28 , 30 ], activation of the angiogenic specific gene [ 10 ], and even autophagy relevant mechanism [ 32 ].…”
Section: Osteogenesis Signaling Pathways Related To Tamentioning
confidence: 99%
“…Both ends of the screw contain a threaded structure, and the middle part contains a porous metal structure. The design of the porous metal structure can increase cell adhesion and promote cell differentiation, and the porous metal structure can also facilitate bone ingrowth so that bone fusion can be completed without the implantation of autologous or allogeneic bone, and related complications in bone harvesting area can be reduced [11,47,48]. The pore size of the porous metal is 150 μm.…”
Section: Segmentmentioning
confidence: 99%